Hand grip strength and all-cause mortality risk in individuals with decreased bone mass: a study from NHANES database - Hongdong Sun; Jiayi Liu; Ruirui Tan; Xiaomei Zhang; Xin Qian; Chenxi Qi; Wei Qi (Frontiers in Medicine)
ObjectivePrevious studies have demonstrated that grip strength is associated with various health outcomes, including osteoporosis. However, the impact of grip strength on long-term mortality risk among individuals with low bone mass remains unclear. This study aims to investigate the association between grip strength and the risk of all-cause mortality in the population with low bone mass.MethodsWe included 1,343 cases of decreased bone mass from the NHANES database spanning 2013 to 2014. All-cause mortality data were ascertained through linkage with national death index records up to December 31, 2015. Analysis was conducted using the Cox proportional hazards regression model, and we assessed result reliability through various model adjustments and hierarchical analyses, Schoenfeld’s global and individual tests are utilized to estimate the time-varying covariance in the Cox proportional hazards regression model’s hypothesis.ResultsThroughout an average follow-up period of 69.5 months, 148 deaths were documented. After adjusting for covariates, a significant association between grip strength and the risk of all-cause mortality was observed in individuals with decreased bone mass (HR = 0.9, 95% CI: 0.87–0.93, p < 0.001). Individuals with normal grip strength, compared to those with low grip strength, exhibited a 56% lower risk of all-cause mortality (HR = 0.44, 95% CI: 0.29–0.67, p < 0.001). Various models consistently demonstrated similar significant trends post-adjustment. Subgroup analysis revealed an interaction between grip strength and coronary heart disease (p < 0.05). Schoenfeld’s global and individual tests confirmed the reliability of the model (p > 0.05).ConclusionOur findings indicate that low grip strength is associated with increased all-cause mortality risk in individuals with decreased bone mass. The inclusion of routine monitoring of grip strength in patients with osteopenia and the encouragement of maintaining or improving grip strength in this population may offer a novel approach to health management for these individuals.